Prevalence and correlates of past 12-month suicide attempt among in-school adolescents in Guatemala - Supa Pengpid (2020)
© 2019 Pengpid and Peltzer. terms.php and incorporate the. Background: The aim of this investigation was to estimate the prevalence of past 12-month suicide attempts and associated factors among in-school adolescents in Guatemala. Methods: Cross-sectional data from the 2014 “Global School-based Health Survey (GSHS)” included 4,274 students (median age 14 years, interquartile range=2 years) that were representative of all middle school students in Guatemala. Results: The prevalence of past 12-month suicide attempt was 16.6%, 12.2% among boys and 20.2% among girls. Among students with a suicide attempt in the past year, 52.8% had a suicide plan in the past year. In adjusted logistic regression analysis, male sex and loneliness were associated with past 12-month suicide attempt, and among boys, none of the variables, and among girls, loneliness and current alcohol use were associated with past 12-month suicide attempt. Conclusion: A high prevalence and several specific factors associated with suicide attempt were identified which can help in guiding preventive strategies.